The Role of Studying the Practical Educational Art of Cooking Course in Developing the Students’ Hygiene Knowledge - محمود، إيمان عبدالمنعم; غانم، محمد صلاح (جامعة الفيوم - كلية السياحة والفنادق, 2013)
مقدمة: تنصب الدراسة على المعارف الصحية لطلاب الفرقة الثانية في أقسام الدراسات الفندقية بثلاثة من معاهد السياحة والفنادق الكبرى بمدينة الإسكندرية خلال العام الجامعي 2011 /2012. أهداف الدراسة: تهدف الدراسة إلى اختبار أثر دراسة الجانب التطبيقي لمقرر فن الطهي الفندقي في تطوير وتنمية المعارف الصحية لطلاب الفرقة الثانية بقسم الدراسات الفندقية، مع الأخذ في الاعتبار أن هؤلاء الطلاب لديهم معارف صحية سابقة من خلال دراستهم لمقرر الصحة العامة )كمتطلب سابق( في السنة الأولي قبل التخصص. منهجية الدراسة: لأغراض الدراسة، تم تقسيم المعارف الصحية لأربعة أقسام: المعارف الخاصة بالتسمم الغذائي، والوعي الصحي الشخصي، والتحكم في درجات الحرارة، والنظافة والتلوث الخلطي للغذاء. ولقد تم توجيه الدعوة لكافة طلاب الفرقة الثانية بقسم الدراسات الفندقية بثلاثة من المعاهد الكبرى بالإسكندرية ) 291 طالب(، للمشاركة في الدراسة مع بداية الفصل الدراسي الأول للعام الجامعي2011/ 2012 ، حيث قام 166 طالب/طالبة فقط )بنسبة استجابة قدرها ( 57.04%بالمشاركة في المقابلة البحثية الأولى. وبنهاية الفصل الدراسي الأول للعام الجامعي نفسه )بعد دراسة مقرر فن الطهي الفندقي لمدة 10 أسابيع ( تم دعوة الطلاب المذكورين ) 166طالب/طالبة( للمشاركة في المقابلة البحثية الثانية، بيد أن 121 طالب/ طالبة فقط )72.89 % بنسبة ( أبدوا الرغبة في المشاركة للمرة الثانية، ومنهم تشكلت عينة الدراسة. النتائج: أكدت نتائج الدراسة -إجمالا - على وجود علاقة إيجابية بين دراسة الجانب التطبيقي لمقرر فن الطهي الفندقي وبين تطوير المعارف الصحية الإجمالية للطلاب محل الدراسة. الخلاصة: المشاركة في الجانب التطبيقي لمقرر فن الطهي الفندقي يؤدي إلى تطور المعارف الصحية الإجمالية للطلاب.
This research paper is closed to 2nd year students of hotel studies departments in 3 high institutes of tourism and hotels in Alexandria during the studying year 2011/2012. Ojective: this paper aimed to examine the effect of studying practical art of cooking course in developing the 2nd year students’ hygiene knowledge. These students had a previous food hygiene knowledge because they were studied a public health course in the 1st year. Methodology: for studying purposes, hygiene knowledge is classified into 4 areas which are: food poisoning knowledge, personal hygiene awareness, temperature control and cross-contamination and cleaning. All 2nd year students in hotel studies departments from 3 high tourism and hotel institutes in Alexandria were invited to participate in this research at the beginning of the 1st term (291 students). Only 166 students (% 57.04) were accepted to participate in the 1st interview. At the end of the first term (after studying the art of cooking course for 10 weeks), all 166 students who participated in the 1st interview are invited to participate in the 2nd interview. Only 121 of them (%72.89) were accepted to participate in the 2nd interview. Results: research results indicated that there is a positive relationship between studying the art of cooking course and the development of the total hygiene knowledge of students. Conclusion: attending the art of cooking course related positively with students’ hygiene knowledge development.
Keywords: الوجبات السريعة -- فن الطهي -- المعارف الصحية